Anaerobic co-digestion of cattle manure with rice straw economic & energy feasibility. - Silvestre, G. (Water Science and Technology)
Rice straw (RS) is one of the most abundant wastes generated in Valencia (Spain). Traditional waste disposal methods are harmful to the environment. The straw burning emits large amounts of toxic air pollutants and the straw burying produces uncontrolled anaerobic fermentation in the soil. The aim of this research was to evaluate the feasibility of cow manure anaerobic co-digestion with RS in a semi-continuous plug flow pilot-scale reactor. Three different periods of co-digestion were carried out as the RS dose was increased. When the addition of RS was 1, 2 and 5% (on weight basis) the biogas productivity increased by 4, 28 and 54% respectively. Furthermore, economic and energy feasibility were analysed considering the logistics cost of the RS (baling, collection, crushing and transportation). Two different scenarios were analysed. In scenario 1, the anaerobic co-digestion process was considered that take place in a new biogas installation, and in scenario 2 the process was considered that take place in a biogas plant already in operation. In scenario 1, the cow manure co-digestion with 2% of RS in a biogas installation of 500 kW showed the best economic analysis (net present value of 13.23%). In scenario 2, the results showed that the maximum distance between the rice field and the biogas plant that produces a positive economic balance was less than 95 km (2% RS) and 74 km (5% RS). In the case of the addition of 1% RS the economic balance is negative. Energy balance is positive in the three mixtures analysed.